Peran Pengusaha Perempuan UMKM dan Pola Pengeluaran Rumah Tangga pada Situasi Bencana Covid-19 - Benedicta Evie; Susy Yunia R. Sanie (University of Merdeka Malang, 2021)
Women as assets of Indonesia's human resources have a crucial role in disaster management. This research is descriptive using a qualitative approach that photograph the adjustment of women's activities based on their role in the current Covid disaster. The research findings shows the informant’s perception that Covid-19 is a disaster, and they are worried, so they try to prevent themselves and their family members from being infected by implementing health protocols. They also provide nutritious food and vitamins as well as a variety of food/drink ingredients that are believed to ward off Covid. Increasing domestic role activities are child care and education. Meanwhile, the public role of economy has undergone adjustments, such as working from home, losing customers or jobs. To be able to survive, adjustments to household expenditure patterns were carried out, namely: increasing the cost of kitchen expenditures, and increase in electricity costs and telephone pulses as the implication of all family members are WFH/SFH online. Reduced expenses: spending on clothes / shoes / bags, cosmetics, and recreation. The social role of the public in this Covid situation is to participate in distributing food to the poor.